Una cita de Sófocles en Los nombres de Cristo de Fray Luis de León - Ruiz Pérez, Ángel (Cuadernos de filología clásica: Estudios griegos e indoeuropeos, 2001)
In fray Luis de León´s On Christ´s Names, there is a quotation from Sophocles which has not received much critical attention: the exact source is identified here (F 755 Radt). The quotation is interesting because it shows that the professor from Salamanca was acquainted with a work by Philo of Alexandria or with its latin translation found in a letter of Saint Ambrose: it is used to chrisianiza the Stoic ethics within fray Luis´s system of ideas.